The Multiplicity of Aswan Pink Clay Pottery (Roman Times to Late Antiquity): Synchronising shape repertoire, clay pastes and firing propertie - Katzjäger, Denise; Peloschek, Lisa; Rembart, Laura (Rei Cretariae Romanae Fautorum Acta, 2017)
The so-called Pink Clay is one of the major clay resources in ancient Egypt and had been just studied recently for the first time in a comprehensive way, integrating archaeological and natural-scientific methods. Regarding ceramic approaches to the material culture of Egypt, Nile mud and Marl clay pottery was in constant focus of studies dealing with the Pharaonic periods in Upper and Lower Egypt. These clays, native to the geological landscape, have been extensively exploited as well in the post-Pharaonic periods, also reported in Aswan at the southernmost edge of the Roman Empire. The detailed analysis of ceramics originating from domestic contexts in ancient Syene and on the nearby island of Elephantine, located in the urban area of modern Aswan, demonstrated the advent of yet another clay in pottery manufacture. The local “Pink Clay”, easily recognizable in hand specimen fabric due to its usually buff pinkish firing colour, is first introduced in the Ptolemaic period, successively gaining importance during the Roman and Late Antique eras. By correlating the diverse clay compositions of Pink Clay and their associated physical properties to its firing behaviour, technological insights into the manufacturing process and technological choices will be acquired. It needs to be investigated in which way the firing procedure had to be executed in order to generate the diagnostic buff pink colour of the ceramics.